CHARACTER EXPLORATION AND STRATEGY OF PLEUROTUS GIGANTEUS MUSHROOMSâ PRODUCT COMMERCIALIZATION ATTRIBUTE DEVELOPMENT AS COMESTIBLES - Rinia Putri, Fernanda
Pleurotus giganteus was found around Geulis Mount, Sumedang, West Java. The cultivation of this mushroom has the potential to be developed as a food source. Furthermore, it will maximize the research purpose in cultivating it. Therefore, this research was held to explore and develop strategies for its character development. Firstly, exploration was held by production simulation. Result showed that the average productivity was 37.39% (fresh weight mushroom per remaining fresh compost weight), average biological efficiency was 72.48% (fresh weight mushroom per dry weight initial substrate). There was residual biomass with a ratio of 0.121 against the net biomass of the fruiting body. The production was carried maximal three times harvest period and the fruiting body was solitary grown. The size of the fruiting body tends to has a uniform size by the low deviation. Next, the harvest yield was tested in organoleptic test. The test was performed to four samples. The difference between samples were determined by the Kruskal Wallis test. The result showed that there was no significant difference in taste (p-value 0.521) and overall (p-value 0.161). There was a significant difference in aroma (p-value 0.02), especially in the P. giganteus cap which has a slightly bad odor. There was also a significant difference in texture (p-value 0.000), especially in P. giganteus stipe. It has a tough texture. The attributes priority was determined by measuring the belief level (bi) and evaluation level (ei) which is furthermore visualized in the Cartesian Diagram of IPA (Importance Performance Analysis). The result showed that the prioritized attributes were good to taste, free from a contaminant, attainable, and have health benefits. The affordable price and chewy texture were at the lowest priority. These results were used to develop the internal and external factor. Then, it was used for develop strategies by using TOWS matrix. These strategies were categorized into four categories, the exploration of basic character, the development as raw material, the development as processed food, and the development of production technology. Analytical Hierarchy Process (AHP) was performed to determine the priority of those strategy categories. AHP was done by the experts' judgment. The result from the highest to lowest priority was the development as processed food (0.411), the development of production technology (0.312), the development as raw material (0.229), and the exploration of basic character (0.049).